Further characterization of the 9q31 microdeletion phenotype; delineation of a common region of overlap containing ZNF462. Issue 3 (3rd December 2022) - Brady, Lauren; Ballantyne, Mark; Duck, John; Fisker, Thomas; Kleefman, Ryan; Li, Chumei; Nfonsam, Landry; Schultz, Lee‐Anne; Tarnopolsky, Mark; McCready, Elizabeth
Abstract: Background: Loss of function variants and whole gene deletions of ZNF462 has been associated with a novel phenotype of developmental delay/intellectual disability and distinctive facial features. Over two dozen cases have been reported to date and the condition is now known as Weiss‐Kruszka syndrome (OMIM# 618619). There are several older reports in the literature and DECIPER detailing individuals with interstitial deletions of 9q31 involving the ZNF462 gene. Many of the characteristic facial features described in these microdeletion cases are similar to those who have been diagnosed with Weiss‐Kruszka syndrome. Methods: We describe three additional patients with overlapping 9q31 deletions and compare the phenotypes of the microdeletion cases reported in the literature to Weiss‐Kruszka syndrome. Results: Phenotypic overlap was observed between patients with 9q31 deletions and Weiss‐Kruszka syndrome. Several additional features were noted in 9q31 deletion patients, including hearing loss, small head circumference, palate abnormalities and short stature. Conclusions: The common region of overlap of microdeletion cases implicates ZNF462 as the main driver of the recognizable 9q31 microdeletion phenotype. The observation of additional features in patients with 9q31 microdeletions that are not reported in Weiss‐Kruszka syndrome further suggests that other genes from the 9q31 region likely act synergistically with ZNF462 to affect phenotypic expression. Abstract : Our study provides evidence that ZNF462 is a main driver of 9q31 microdeletion associated phenotypes but that additional genes in the 9q31 region may act synergistically with ZNF462 to affect phenotypic expression. There is increasing evidence that ZNF462 haploinsufficiency causes a spectrum of phenotypes now recognized as Weiss‐Kruszka syndrome. Although several similarities are noted between patients with 9q31 microdeletions and Weiss‐Kruszka syndrome, pheonotypic differences are highlighted that suggests 9q31 microdeletions represent a recognizable contiguous gene deletion syndrome.